Influence of new media on intercultural communication: an example of an Erasmus student - Seyfi, Murat; Güven, Deniz (Information & Media, 2016)
The world turns out to be a small village due to globalisation and communication technologies. In this new world, different cultures and communication means have interlaced and started to increasingly affect each other, leading communication and culture to transform into two organic structures that feed each other. The culture in which individuals socialise also determines these individuals’ ways of communication. It is necessary to examine the communicational behaviours of the members of given societies to distinguish the differences between these cultures. The skills of different people who live in different cultures in enduring the information load would also be different. Today, it is possible to transfer any information via news media in an instant. This, as a result, increases the significance of new media in intercultural communication. This study is to examine the influence of social media usage in the intercultural adaptation process of Erasmus students who came to Turkey for educational purposes. Within this scope, detailed analyses were made using both qualitative and quantitative research methods.
Keywords: intercultural communication; Erasmus students; new media